Deficient auditory predictive coding during vocalization in the psychosis risk syndrome and in early illness schizophrenia: the final expanded sample. Issue 11 (25th September 2018) - Mathalon, Daniel H; Roach, Brian J; Ferri, Jamie M; Loewy, Rachel L; Stuart, Barbara K; Perez, Veronica B; Trujillo, Tara H; Ford, Judith M
Abstract: Background: During vocalization, efference copy/corollary discharge mechanisms suppress the auditory cortical response to self-generated sounds. Previously, we found attenuated vocalization-related auditory cortical suppression in psychosis and a similar trend in the psychosis risk syndrome. Here, we report data from the final sample of early illness schizophrenia patients (ESZ), individuals at clinical high risk for psychosis (CHR), and healthy controls (HC). Methods: Event-related potentials (ERP) were recorded from ESZ ( n = 84), CHR ( n = 71), and HC ( n = 103) participants during a vocalization paradigm. The N1 ERP component was elicited during production (Talk) and playback (Listen) of vocalization. Age effects on N1 suppression (Talk–Listen), Talk N1, and Listen N1 were compared across groups. N1 measures were adjusted for normal aging before testing for group differences. Results: Both ESZ and CHR groups showed reduced Talk–Listen N1 suppression relative to HC, but did not differ from each other. Listen N1 was reduced in ESZ, but not in CHR, relative to HC. Deficient Talk–Listen N1 suppression was associated with greater unusual thought content in CHR individuals. N1 suppression increased with age in HC (12–36 years), and while CHR individuals showed a similar age-related increase, no such relationship was evident in ESZ. Conclusions: Putative efference copy/corollary discharge-mediated auditory cortical suppression during vocalization is deficient in ESZ and precedes psychosis onset, particularly in CHR individuals with greater unusual thought content. Furthermore, this suppression increases from adolescence through early adulthood, likely reflecting the effects of normal brain maturation. This maturation effect is disrupted in ESZ, presumably due to countervailing illness effects.